Country Insurance Using Financial Instruments - Ricci, Luca.; Chamon, Marcos; Zhang, Yuanyan (Washington, D.C. : International Monetary Fund, 2011)
The availability of financial instruments related to indices that track global financial conditions and risk appetite can potentially offer countries alternative options to insure against external shocks. This paper shows that while these instruments can explain much of the in-sample variation in borrowing spreads, this fails to materialize in hedging strategies that work well out-of-sample during tranquil times. However, positions on instruments such as those tracking the US High Yield Spread, the VIX, and especially other emerging market CDS spreads can substantially offset adverse movements in own spreads during times of systemic crises. Moreover, high risk countries seem to gain more, as their underlying weaknesses makes them more vulnerable to external shocks. Overall, the limited value in tranquil times, coupled with political economy arguments and innovation costs could justify the limited interest for this type of hedging in practice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet